The Advanced Analysis of Deep Drawing Processes for 1-Inch Diameter Dop-Pipe Caps: Simulation and Experimental Insights - Pratama, Tito Chaerul; Sukarman; Tikamori, Ghazi; Mulyadi, Dodi; Supriyanto, Agus; Amir, Amir; Khoirudin, Khoirudin; Hananto, Agus (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2024)
This article investigates the challenges and solutions within the deep drawing process, focusing on issues like cracks and deviations from standard thickness dimensions. Utilizing both experimental methods with a 40-ton power press machine and numerical simulations via ABAQUS software, the study uses SPCC-SD steel to produce a Dop-pipe 1-inch diameter pipe cap. Key findings reveal significant correlations in elements E-90 and E-91, with minimal disparities of around 4.5% between experimental and numerical approaches, showcasing the accuracy of numerical predictions. Notably, the numerical simulations identify potential issues such as increased thickness due to higher axial forces, providing valuable insights for process optimization and defect reduction. By advancing the deep drawing process and extending its applicability to broader material-forming applications, this research contributes significantly to enhancing production efficiency and improving manufacturing practices, emphasizing the importance of simulation-driven approaches in achieving precision and quality enhancement in complex manufacturing processes.